2014
DOI: 10.12816/0008228
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Minimum Inhibitory Concentration of Cycloserine in Multidrug Resistant Mycobacterium Tuberculosis Isolates

Abstract: This study was performed to determine the minimum inhibitory concentration (MIC) of cycloserine on 48 multidrug resistant tuberculosis (MDR-TB) isolates using the Broth Microdilution Method. No relationship between specific concentrations of cycloserine administrated and the bacterial inoculums used was found. This implied that the clinical isolates were obtained from patients on different treatment regimens. The findings of this study would potentially be important in alleviating the toxic effects of cycloser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Previous studies on wild-type M. tuberculosis found MIC values for DCS equal to 15 μ g/mL, 18 while MDR-TB clinical isolates exhibited MIC values ranging from 32 to 64 μ g/mL. 37 In general, laboratory strains are more susceptible to antibiotics than clinically isolated strains, such as MDR-TB strains. Similar experiments revealed that LCS exhibits a ∼10-fold better inhibitory growth effect than DCS, with a MIC value of 0.3 μ g/mL (Table S1).…”
Section: Resultsmentioning
confidence: 94%
“…Previous studies on wild-type M. tuberculosis found MIC values for DCS equal to 15 μ g/mL, 18 while MDR-TB clinical isolates exhibited MIC values ranging from 32 to 64 μ g/mL. 37 In general, laboratory strains are more susceptible to antibiotics than clinically isolated strains, such as MDR-TB strains. Similar experiments revealed that LCS exhibits a ∼10-fold better inhibitory growth effect than DCS, with a MIC value of 0.3 μ g/mL (Table S1).…”
Section: Resultsmentioning
confidence: 94%
“…The mean number of drugs (percentage coefficient of variation) detected at each lung cavity position was 3.0 (59.0%), whereas those above lower limit of quantitation were 2.8 (64.8%) (drugs shown in Figure E4). The mean number of drugs with effective concentrations above the lowest MIC in epidemiologic study distributions reported in the literature fell to 2.1 (70.6%) drugs (P , 0.01), shown by cavity position in Figure 1H (24,30,(36)(37)(38). Because all patients were receiving at least eight drugs, this means that penetration into the cavity was highly variable.…”
Section: Cavity Dissection and Drug Concentrations In Lung Cavitiesmentioning
confidence: 90%
“…MICs were determined (Betts and Wareham, 2014; Singh, 2014; Singh et al, 2017) using the National Committee for Clinical Laboratory Standards (2002) susceptibility testing guidelines in 96-well microtiter plates (SPL Life Sciences, Pocheon, South Korea). Briefly, an overnight culture at a dilution of 1:100 inoculated in TSB was cultured for 24 h in the presence of curcumin (100, 200, or 500 μg/ml) at 37°C.…”
Section: Methodsmentioning
confidence: 99%